Risk Management in the System of Tourist Business Control - TSAPOVA, Olga Alexandrovna; KADOCHNIKOVA, Valeriia Petrovna; KENDYUKH, Yevgeniy Ivanovich; GORKOVENKO, Lyudmila Alexandrovna; SHARIPOV, Ruslan Maratovich; SAULIUS, Nefas (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
Any business is at risk, however, tourism business is the most risky, because it differs in latitude, cause of occurrence and other indicators, and all this accumulates into possible negative results which come after they occur.  Risk management is a planned process in which organizations manage active crises. A crisis is defined as a time of difficulties or danger, and usually this is the time when you need to make difficult or dangerous decisions. By having a plan that describes the crisis management process, organizations can more easily adapt to the crisis.